Role of Civil Society in Gender Equality: Sociological Perspectives - Ziyauddin, K. M. (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
Compared to previous studies on gender equality, such as work, democracy, and welfare, or caste, religion, and family, the studies have placed little or no attention on the connections between civil society organisations, and gender equality or even on relationships between civil society bodies/organisations and gender equality has garnered little or no attention. In this paper, I propose a paradigm for analysing the role of civil society in gender equality, in which civil society is viewed as a critical pillar in advancing the cause and providing the wheels that propel gender equality for men and women (he or she). On the one hand, gender mainstreaming, which is concerned with the study of gender equality practises both inside and outside of organisations, in economic spheres, political activism, parting roads in governance, and volunteerism in activities and projects aimed at promoting gender equality in the larger community, is important